Development of a Web Application for Online Product Distribution: A Case Study of The Roof Project - อรุณโชติ, วรภัฎ; ปานสุวรรณ, ดุสิตา (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research aimed to: 1) develop a web application for online product distribution of rubber sealing sheets for leak repair for The Roof Project as a case study, 2) evaluate the efficiency of the web application by experts, and 3) examine user satisfaction toward the web application. The sample consisted of information technology experts and users who tested the web application. The research instruments included the developed web application, a system quality assessment form, and a user satisfaction questionnaire based on a five-point Likert scale. Data were analyzed using mean and standard deviation.           The results revealed that the developed web application achieved a high level of quality (x̄= 3.88, S.D. = 0.64). The overall user satisfaction was also at a high level (x̄= 3.98, S.D. = 0.67). These findings indicate that the developed web application is efficient and appropriate for practical implementation to enhance product distribution channels and support business operations in an e-commerce environment.